Journey from natural numbers to complex numbers - Shah, Nita H.; Vishnuprasad, Thakkar D. (Boca Raton : CRC Press, 2021)
"This book covers the fundamentals, proof of theorems, examples, definitions, and concepts. It explains the theory in an easy and understandable manner and offers problems for understanding and extensions of concept are included. The book provides concepts in other fields and includes an understanding of handling of numbers by computers. Research scholars and students working in the fields of engineering, science, and different branches of mathematics will find this book of interest, as it provides the subject in a clear and concise way"--
4.5 Binary Operations in Cuts -- 4.6 Least Upper Bound Property -- 4.7 Set of Cuts as Extension of Rational Numbers -- 4.8 Cardinality of Set of Real Numbers -- 4.9 Limitations of Real Numbers -- 4.10 Summary -- Chapter 5 Complex Numbers -- 5.1 Complex Numbers as Ordered Pairs of Real Numbers -- 5.2 Binary Operations in Complex Numbers -- 5.3 Introduction of Imaginary Numbers -- 5.4 Representation of Complex Numbers -- 5.5 Ordering in Complex numbers -- 5.6 Cardinality of the Set of Complex Numbers -- 5.7 Algebraic Numbers -- 5.8 Summary -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Numbers, Natural; Numbers, Complex; MATHEMATICS / Applied; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Operations Research